Performance evaluation of small and medium-sized enterprises according to the entrance of the scorecard applied study in company Al fadly for construction industries - عبد الرضا نغم يوسف; كاظم حميد مظلوم (Journal of Economics and Administrative Sciences, 2016)
The research Aim is to provide support to small enterprises by providing tools that enable measurement and test their performance and identifying weaknesses and work on them is determined by the problem of searching using traditional assessment methods for small projects with only financial performance measurement standards that do not provide a complete picture of the performance of these projects so use the balanced scorecard the four pillars (financial, customer, learning and growth, and internal processes) and identify deviations and work on them through the use of the outputs of the programme (probe), PROmoting Business Excellence-PROBE), which It is a model of performance evaluation, with which you can develop performance company, and a research tool in the roots of the problems and poor performance), the importance of research demonstrated through its application in evaluating the company’s performance considered as well as learn how successful small businesses in managing their work and find out how their To achieve its goals. Methods used in the research programme has been used (probe), which includes the four perspectives of the balanced scorecard used in evaluation and on the basis of which it was the analysis of the results obtained. The research has reached a set of conclusions which, in some aspects of the scorecard and perspectives of b (level of financial performance, customer growth impairment, impaired the performance of the management company for the planning function, particularly in the management of its internal operations, and therefore not to manage its resources efficiently, and found out that most small businesses rely significantly on traditional financial indicators in gauge and see their performance which gives a clear picture of its performance. On the basis of these conclusions, built a set of recommendations including the need for a serious and rapid adjustments to those aspects, as well as the success of SME needs to know and embrace the culture of the balanced scorecard in General, and specific research particularly, the need to create a local program to assess performance, special balmo’ossat Iraqi Government to measure and see the performance of small enterprises in the country for various sectors.